Potency and durability of T and B cell immune responses after homologous and heterologous vector delivery of a trimer-stabilized, membrane-displayed HIV-1 clade ConC Env protein - Perdiguero, Beatriz; Hauser, Alexandra; Gómez, Carmen Elena; Peterhoff, David; Sideris, Elefthéria; Sorzano, Carlos Óscar S.; Wilmschen, Sarah; Schaber, Marion; Stengel, Laura; Asbach, Benedikt; Ding, Song; Von Laer, Dorothee; et al. (Frontiers in Immunology, 2023)
The generation of a HIV-1 vaccine able to induce long-lasting protective immunity remains a main challenge. Here, we aimed to modify next generation soluble, prefusion-stabilized, close-to-native, glycan-engineered clade C gp140 envelope (Env) trimers (sC23v4 KIKO and ConCv5 KIKO) for optimal display on the cell surface following homologous or heterologous vector delivery. A combination of modifications, (i) replacing the natural cleavage site by a native flexible linker and introducing a single amino acid substitution to prevent CD4 binding (*); (ii) fusing a heterologous VSV-G-derived transmembrane moiety to the gp140 C-terminus; and (iii) deleting 6 residues proximal to the membrane, scored best regarding the preservation of closed, native-like Env trimer conformation and antigenicity when using a panel of selected broadly neutralizing (bnAb) and non-neutralizing (nnAb) monoclonal antibodies for flow cytometry. When delivering membrane-tethered sC23v4 KIKO* and ConCv5 KIKO* via DNA, VSV-GP and NYVAC vectors, the two native-like Env trimers provide differential antigenicity profiles. Whereas such patterns were largely consistent amongst the different vectors for either Env trimer, the membrane-tethered ConCv5 KIKO* trimer adopted a more closed and native-like structure than sC23v4 KIKO*. In immunized mice, VSV-GP and NYVAC vectors expressing the membrane-tethered ConCv5 KIKO* administered in prime/boost combination was the most effective regimen for the priming of Env-specific CD4 T cells amongst all tested combinations. The subsequent booster administration of trimeric ConCv5 KIKO* Env protein preserved the T cell activation levels between groups. The evaluation of the HIV-1-specific humoral responses induced in the different immunization groups after protein boosts showed that the various prime/boost protocols elicited broad and potent antibody responses, preferentially of a Th1-associated IgG2a subclass, and that the obtained antibody levels remained high at the memory phase. In summary, we provide a feasible strategy to display multiple copies of native-like Env trimers on the cell surface, which translates into efficient priming of sustained CD4+ T cell responses after vector delivery as well as broad, potent and sustained antibody responses following booster immunizations with the homologous, prefusion-stabilized close-to-native ConCv5 KIKO* gp140 Env trimer.